2007
DOI: 10.1002/pssc.200674730
|View full text |Cite
|
Sign up to set email alerts
|

GaN/air gap based micro‐opto‐electro‐mechanical (MOEM) Fabry‐Pérot filters

Abstract: Structural and optical properties of Fabry-Pérot filters (FPFs) with GaN/air gap based distributed Bragg reflectors (DBRs) were studied. Reflectance of GaN/air gap DBRs on sapphire substrate was calculated from the standard transmission matrix method and results showed that 98% reflectance is achievable with only 3.5 pairs at a center wavelength of 450 nm. The thickness of the GaN layer and the first AlN layer was determined according to the deformation induced by the residual stress. In-plane strain correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…AlN/GaN short period-superlattice ͑SPS͒ structures are employed in distributed Bragg reflectors ͑DBRs͒ which are considered to be a key element in nitride optoelectronic devices such as vertical cavity surface emitting lasers, resonant cavity surface emitting diodes resonant cavity and tunable detectors. 6 This type of an AlN/GaN superlattice also serves as an interlayer in order to compensate for the strain arising between two lattice mismatched layers such as in the case of GaN deposited directly on sapphire or silicon.…”
mentioning
confidence: 99%
“…AlN/GaN short period-superlattice ͑SPS͒ structures are employed in distributed Bragg reflectors ͑DBRs͒ which are considered to be a key element in nitride optoelectronic devices such as vertical cavity surface emitting lasers, resonant cavity surface emitting diodes resonant cavity and tunable detectors. 6 This type of an AlN/GaN superlattice also serves as an interlayer in order to compensate for the strain arising between two lattice mismatched layers such as in the case of GaN deposited directly on sapphire or silicon.…”
mentioning
confidence: 99%
“…A study is being conducted on the single-mode micro waveguide of the Silicon microstructure core, Sapphire layer is cladding to optimize waveguide features and optical refractive indices [TE0, TM0 polarization]. It appears that the effective index plays a significant role in providing waveguide along with the slab, according to the analyzed waveguide modes are confined within the higher index of refraction of the Silicon middle layer, which is illustrated in Figure 4a in 2D [8,9]. Also, Figure 4b indicates how the mode distributes over (Silicon on sapphire) in 2D, and which depicted how the energy of modes accumulated in high refractive index, this is very useful for the optical fiber.…”
Section: Resultsmentioning
confidence: 99%
“…However, these depend on a refractive index difference of only 0.2 or less between adjacent layers, compared to the difference of ∼1.4 in GaN-air structures. Cho et al reported simulated reflectance spectra for the latter type of structure, showing that peak reflectivities at 450 nm reach essentially 100% with as few as 4 repeat periods [10].…”
Section: Introductionmentioning
confidence: 99%